In Situ and Quantitatively Imaging of Heat‐Induced Oxidative State and Oxidative Damage of Living Neurons Using Scanning Electrochemical Microscopy. Issue 12 (14th November 2022) - Zhang, Junjie; Liu, Yulin; Li, Yabei; Zhu, Tong; Qiu, Jinbin; Xu, Feng; Zhang, Hua; Li, Fei
Abstract: Central nervous system is sensitive and vulnerable to heat. Oxidative state and oxidative damage of neurons under heat stress are vital for understanding early consequences and mechanisms of heat‐related neuronal injury, which remains elusive partly due to the technical challenge of in situ and quantitative monitoring methods. Herein, a temperature‐controlled scanning electrochemical microscopy (SECM) platform with programmable pulse potential and depth scan modes is developed for in situ and quantitatively monitoring of oxygen consumption, extracellular hydrogen peroxide level, and cell membrane permeability of neurons under thermal microenvironment of 37–42 °C. The SECM results show that neuronal oxygen consumption reaches a maximum at 40 °C and then decreases, extracellular H2 O2 level increases from 39 °C, and membrane permeability increases from 2.0 ± 0.6 × 10 −5 to 7.2 ± 0.8 × 10 −5 m s −1 from 39 to 42 °C. The therapeutic effect on oxidative damage of neurons under hyperthermia conditions (40–42 °C) is further evaluated by SECM and fluorescence methods, which can be partially alleviated by the potent antioxidant edaravone. This work realizes in situ and quantitatively observing the heat‐induced oxidative state and oxidative damage of living neurons using SECM for the first time, which results can contribute to a better understanding of the heat‐related cellular injury mechanism. Abstract : A temperature‐controlled scanning electrochemical microscopy platform with developed programmable pulse potential and depth scan modes is applied for in situ and quantitatively imaging the heat‐induced oxidative state and oxidative damage of a single living neuron at 37–42 °C.